Impact and sustainable growth in social initiatives: Lipor´s crew project - Ahamad, Nasser Mohez (2022)
CREW is the partnership program between Lipor and ERP Portugal to repair and donate Waste from Electrical and ElectronicEquipment to social mediators. This work project intends to identify how impact is generated and measured in social initiatives and how they can grow sustainably. It is divided into three sections. The case study displays CREW's progress from its creation until the year-end of 2020, showcasing its limitations and success factors. The teaching note aims to provide the teaching staff with all the necessary information to achieve its pedagogical goals. The project evaluation report is meant to define practical strategies so that CREW can achieve a higher social return.